Prenatal nursing consultation: care for pregnant women with syphilis (Research, Society and Development, 2022)
Objective: To identify the actions of nurses during prenatal consultations for pregnant women with syphilis Methodology: This is an exploratory, descriptive research with a qualitative approach, carried out with eight nurses who provide prenatal care in a city in the Southwest region of the State of Paraná. Data collection took place in May 2021 and the interview was recorded and transcribed later. Data were analyzed using the thematic analysis technique. Results and Discussion: Nurses perform nursing consultations during prenatal care and pay attention to protocols for early detection and treatment of syphilis in pregnancy. Pregnant women are advised about the disease, as well as the need for early treatment of their partner and their partner to avoid vertical transmission and possible problems with the newborn. Conclusion: It is necessary to emphasize the active search of pregnant women for an early start of prenatal care to avoid harm. Care practices can reflect on the quality of care and health indicators.